Extranodal Lymphomas: a pictorial review for CT and MRI classification - Reginelli, Alfonso; Urraro, Fabrizio; Sangiovanni, Angelo; Russo, Gaetano Maria; Russo, Carolina; Grassi, Roberta; Agostini, Andrea; Belfiore, Maria Paola; Cellina, Michaela; Floridi, Chiara; Giovagnoni, Andrea; Sica, Antonello; et al. (Acta Biomedica Atenei Parmensis, 2020)
Extranodal lymphomas represent an extranodal location of both non-Hodgkin and Hodgkin lymphomas. This study aims to evaluate the role of CT and MRI in the assessment of relationships of extranodal lymphomas with surrounding tissues and in the characterization of the lesion. We selected and reviewed ten recent studies among the most recent ones present in literature exclusively about CT and MRI imaging of extranodal lymphomas. Contrast-enhanced computed tomography (CT) is usually the ﬁrst-line imaging modality in the evaluation of extranodal lymphomas, according to Lugano classification. However, MRI has a crucial role thanks to the superior soft-tissue contrast resolution, particularly in the anatomical region as head and neck.